Caring for Patients with Depression in Primary Care - Kroll, David S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Depression is the leading cause of disability in the United States, and the traditional framework for managing depression within a psychiatry practice i.e., a single psychiatrist treating a single patient for up to an hour per week comes up painfully short at the level of serving the population even if it can be highly effective for individuals. At the same time, the non-systematic way in which most patients identify the need to see a specialty provider in behavioral health leaves many stranded, regardless of how complex their needs are. Primary care is now often considered the de facto mental health system in the United States, and primary care providers have been charged with the impossible task of making up for the dearth of psychiatric specialty providers and somehow correcting the many inequities in access to care that remain. Primary care providers shouldn t have to do this alone. Help can come in many forms, of course, and some primary care practices are lucky enough to have a consulting psychiatrist on-site, available to answer any questions that come up and see patients directly when they need an expert opinion. This is exactly what David S Kroll, MD, an Associate Vice Chair in the Department of Psychiatry at Brigham and Women s Hospital in Boston and an Assistant Professor at Harvard Medical School, does for a primary care practice that serves more than 17,000 patients with a wide range of medical, social, and psychiatric problems. But most primary care practices don t have this resource. This book replicates the expertise of a consulting psychiatrist in a concise volume that primary care providers can pull off their shelves whenever they have a question about managing depression. It ensures that no one has to do this on their own. Managing Depression in Primary Care contains fourteen chapters that anticipate the questions, problems, and practical challenges that are most likely to come up when managing depression in primary care. It covers the basic skills that are needed for treating depression when it occurs in a vacuum, but it also provides practical guidance on treating depression in the real world where it will inevitably be complicated by other factors. It also covers important associated topics including suicide, substance use, and disability.
Keywords: Primary care (Medicine).; Psychiatry; Primary Care Medicine; Psychiatry; Depression; Primary Health Care; Psychiatry